2005
DOI: 10.1038/sj.onc.1209057
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification of MET with boundaries within fragile site FRA7G and upregulation of MET pathways in esophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EA) is characterized by a poor prognosis making the identification of clinically targetable proteins essential for improving patient outcome. We report the involvement of multiple alterations of the MET pathway in EA development and progression. Microarray analysis of Barrett's metaplasia, dysplasia, and EA revealed overexpression of the MET oncogene in EAs but only those with MET gene amplification. STSamplification mapping revealed that the boundary of the MET amplicon in these EAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 40 publications
2
96
0
1
Order By: Relevance
“…One particular translocation, the translocated promoter region-MET translocation, and MET amplification have been reported in gastric, oesophageal and non-small cell lung cancers. [9][10][11][12] Germ-line and somatic MET mutations are found in papillary renal, gastric and childhood hepatocellular cancers. [13][14][15] However, constitutive MET activation is primarily induced by transcriptional up-regulation or HGF-dependent autocrine/paracrine loop mechanisms.…”
mentioning
confidence: 99%
“…One particular translocation, the translocated promoter region-MET translocation, and MET amplification have been reported in gastric, oesophageal and non-small cell lung cancers. [9][10][11][12] Germ-line and somatic MET mutations are found in papillary renal, gastric and childhood hepatocellular cancers. [13][14][15] However, constitutive MET activation is primarily induced by transcriptional up-regulation or HGF-dependent autocrine/paracrine loop mechanisms.…”
mentioning
confidence: 99%
“…Or, alternatively, did the drug induce a stress able to promote DNA breaks in fragile sites such as the one in which the MET gene is located ( 34 )? To answer these questions, Turke and colleagues ( 35 ) analyzed the HCC827 NSCLC cell line that, upon gefi tinib treatment, became resistant via MET amplifi cation.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…[1][2][3] However, to date, it is thought that somatic mutation of MET is a rare event in the sporadic primary carcinomas of adults, including ovarian carcinomas, 4,5 with papillary carcinoma of the kidney being an exception. 6 On the other hand, MET amplification was identified in 5-10% of gastric cancers, 7-9 4% of esophageal cancers, 10 3-4% of lung cancers, 11,12 and 10% of colorectal cancers. 13 Our recent study identified that MET overexpression and gene amplification were commonly detected in ovarian clear-cell adenocarcinoma, with their frequencies at 22 and 24%, respectively.…”
mentioning
confidence: 99%